Menos plata pero más papas: consecuencias económicas de la independencia en el Perú - Contreras, Carlos (2011)
This articles is divided into two sections: the first presents the most solid quantitative series on Peruvian production and commerce during the transitional period of independence. From the series is can be deduced that emancipation brought with it a contraction of production and commerce which was prolonged well into the second half of the nineteenth century. The second section deals with the characteristics of the state political economy after independence, particularly between 1821 and the 1870s. What stands out is official state neutrality with regards to mining and fiscal mitigation. These measures provoked complaints at the time and brought about the contraction mentioned above. But it also meant a certain amount of wellbeing for the Indians which was manifested in their demographic growth during the nineteenth century.